2015
DOI: 10.1108/jmp-12-2012-0404
|View full text |Cite
|
Sign up to set email alerts
|

From person-environment misfit to job burnout: theoretical extensions

Abstract: 2015),"Effects of intrinsic and extrinsic motivation on task and contextual performance of Pakistani professionals: The mediating role of commitment Aaron Cohen, Mohamed Abedallah, (2015),"The mediating role of burnout on the relationship of emotional intelligence and self-efficacy with OCB and performance", Management Research Review, Vol. 38 Iss 1 pp. 2-28 http://dx.If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 42 publications
2
55
0
Order By: Relevance
“…Optimism was measured with a published Chinese version of the 6-item subscale of the Psychological Capital Scale (Luthans, Youssef, & Avolio, 2007;Tong, Wang, & Peng, 2015). A sample item is: 'I always look on the bright side of things regarding my job.…”
Section: Optimismmentioning
confidence: 99%
“…Optimism was measured with a published Chinese version of the 6-item subscale of the Psychological Capital Scale (Luthans, Youssef, & Avolio, 2007;Tong, Wang, & Peng, 2015). A sample item is: 'I always look on the bright side of things regarding my job.…”
Section: Optimismmentioning
confidence: 99%
“…Pertaining to questions related to the subcategory of cynicism, most athletic department employees have not lost interest, become less enthusiastic, or doubted the significance of their jobs. A strong desire to work in athletics coupled with a strong person-environment fit may have a positive effect on mitigating workplace burnout and cynicism (Tong et al 2015) and might also explain the overall sentiments of not feeling burned out or cynical, as expressed by the employees of athletic departments in this study.…”
Section: Burnout Outcomesmentioning
confidence: 86%
“…Ryska (2009) found that the adoption of a highly collaborative leadership style within athletic department roles may contribute to low levels of burnout. Additionally, burnout has been found to result from the misalignment of the work setting (Tong, Wang & Peng 2015).…”
Section: Burnout Outcomesmentioning
confidence: 99%
“…P‐O misfit thus involves an experience of cognitive dissonance as employees are forced to negotiate between their personal identity, which differentiates the individual from others within a social context, and their aspired social identities, which categorize the self into “more inclusive social unites that depersonalize the self‐concept” (Brewer, , p. 476). Given the salience of humans’ need for affiliation and belonging, individuals low on P‐O fit likely face an ongoing internal tension to adjust their self‐concepts to the depersonalizing demands of their work environment, a process that over time may ultimately lead to a decline in self‐definition and hence burnout (Tong, Wang, & Peng, ). The cognitive dissonance experienced is believed to evoke role conflict, and the associated anxiety and uncertainty is particularly prominent in explaining exhaustion as employees feel a lack of resources to help them cope in their environment (Tong et al, ).…”
Section: High‐involvement Work Practices and Well‐beingmentioning
confidence: 99%
“…Over time, this ensures that they feel alienated and experience a lack of engagement, which is expressed by a cynical attitude or withdrawal behavior, that is, depersonalization (Schaufeli & Enzmann, ). Indeed, as P‐O fit enhances one's self‐definition by virtue of belonging, it may act as an important resource for employees to ameliorate their defensive coping, eventually resulting in less emotional exhaustion and depersonalization over time (Tong et al, ). In accordance with the theoretical perspectives and empirical evidence outlined above, we hypothesize that:
Hypothesis 2: Positive perceptions of P‐O fit will be negatively related to (a) emotional exhaustion and (b) depersonalization .
…”
Section: High‐involvement Work Practices and Well‐beingmentioning
confidence: 99%